Students’ Perceptions Toward Blended Learning Through Youtube - Dewirahmadanirwati, Dewirahmadanirwati; Nusi , Ahmad; Novia, Novia; Ardi, Havid (Jurnal Ilmiah Langue and Parole, 2024)
This study explores the perceptions of students towards blended learning using YouTube as a teaching tool. Blended learning, which combines traditional face-to-face teaching with online methods, has emerged as a promising approach to address these challenges. Blended learning allows students to access course materials and engage in activities both in the classroom and through digital platforms like YouTube. This study, conducted at Ekasakti University with 54 students divided into three groups, employed questionnaires, interviews, and observations to gather comprehensive data. The findings indicate a generally positive perception among students towards the use of YouTube in blended learning. Students recognize the benefits of YouTube in enhancing language learning experiences, as evidenced by high mean scores for statements emphasizing its effectiveness. However, concerns were raised regarding certain aspects of using YouTube, reflected in consistently low mean scores for specific statements across all groups. Addressing these concerns is crucial for optimizing the effectiveness of blended learning with YouTube and ensuring its successful integration into educational practices. Overall, while students largely appreciate the benefits of blended learning with YouTube, addressing their concerns is essential to further enhance its effectiveness and promote student engagement and learning outcomes.